Development and promotion of rural tourism through European funds in Romania - Elena Sima (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 7th Edition of the International Symposium, November 2016, Bucharest, 2016)
Romania has a great tourism potential, but unfortunately this potential has not been explored enough. The objective of this paper is to analyze how the European funds were accessed for developing and promoting tourism activities in rural areas at national level. The work is based on the data processed according to the European Commission Statistics (Eurostat) and the national statistics. The databases published by the Ministry of Agriculture and Rural Development and different organizations in the field were also investigated. The research methods were represented by data collection, mainly online data, data processing, centralization and synthetic presentation (under tabular form). The investments in rural tourism have a great advantage, i.e. job creation and maintaining the local (rural) labour, revitalization of rural localities, mainly those from the less-favoured and remote rural areas.
Keywords: Q14; L83; R58; 330; European funds; rural tourism; investments; tourism infrastructure; Romania